Conduct Problem Pada Siswa SMA di Kabupaten Pasaman Sumatera Barat - Dian Eka Putri; Rizanda Machmud (Jurnal Endurance, 2019)
Teenagers have a tendency to do things that are destructive to themselves and others, called behavioral problems (conduct problems). As many as 20% of adolescents in the world experience mental health problems and behavior problems (conduct problems). This study aims to obtain an overview of the factors associated with conduct problems in high school students in Pasaman Regency. The study design was cross sectional. The number of respondents was 336 high school students in Pasaman Regency. The sampling technique is Proportional Random Sampling. Data collection was carried out using a questionnaire. Data analysis using chi square technique and logistic regression with Backward Stepwise method. The results showed that there was a significant relationship between parenting (P value 0,041 OR 2, 205), school environment ( p value 0,000 OR 3,797 ), peer environment ( p value 0,000 OR 7,323), economic status ( pvalue 0,027 OR 2,125 ) and conduct problems. Peer environment is the most related factor in conduct problems with an OR score of 6.089. The conclusion in this resarch is that there is a significant relationship between the family environment: parenting with conduct problems, there is a significant relationship between peer environment and conduct problems, there is a significant relationship between the school environment and conduct problems, there is a significant relationship between economic status and conduct problems. Remaja memiliki kecenderungan untuk melakukan perbuatan yang merusak bagi dirinya dan orang lain yang disebut dengan conduct problem. Sebanyak 20% remaja di dunia mengalami masalah kesehatan mental dan conduct problem. Penelitian ini bertujuan untuk memperoleh gambaran faktor-faktor yang berhubungan dengan conduct problem pada siswa SMA di Kabupaten Pasaman Desain penelitian adalah cross sectional. Jumlah responden adalah 336 siswa SMA di Kabupaten Pasaman. Teknik pengambilan sampel adalah Proporsional Random Sampling. Pengumpulan data dilakukan menggunakan kuesioner. Analisis data dengan teknik chi square dan regresi logistik dengan metode Backward Stepwise. Hasil penelitian didapatkan ada hubungan signifikan pola asuh (P value 0,041 OR 2, 205) lingkungan sekolah ( p value 0,000 OR 3,797 ), lingkungan teman sebaya ( p value 0,000 OR 7,323) status ekonomi ( pvalue 0,027 OR 2,125 ) dengan conduct problem. Teman sebaya merupakan faktor yang paling berhubungan dengan OR 6,089. Kesimpulan penelitian diketahui terdapat hubungan signifikan antara lingkungan keluarga : pola asuh dengan conduct problem, terdapat hubungan signifikan antara lingkungan teman sebaya dengan conduct problem, terdapat hubungan signifikan antara lingkungan sekolah dengan conduct problem, terdapat hubungan signifikan antara status ekonomi dengan conduct problem.